Blood and intestinal parasites of squirrels (Rodentia : Sciuridae) in Amazonian Brazil - Lainson, Ralph (Instituto Oswaldo Cruz, 2019)
We report the result of an examination for blood and intestinal protozoa in 12 specimens of the red squirrel Sciurus spadiceus (Rodentia: Sciuridae) from Birroque, municipality of Pl?cido de Castro, state of Acre, Brazil. No parasites were detected in thin, Giemsa-stained blood films of the animals, but culture of the blood of three in Difco B45 medium blood-agar slants gave rise to isolates of epimastigotes. Inoculation of one isolate into laboratory mice resulted in the appearance of Trypanosoma cruzi-like trypomastigotes in their peripheral blood, and the other two isolates gave rise to transient infections with a T. lewisi-like parasite in inoculated mice and hamsters. The failure of the latter parasite to develop in the triatomine bug Rhodnius robustus suggests that it is probably not T. rangeli. This appears to be the first record of a T. lewisi-like trypanosome in neotropical squirrels. Oocysts of an Eimeria sp., were detected in the faeces of 10 animals (83.3%). The parasite develops in the epithelial cells of the intestine, where it may cause severe damage and sometimes results in death of the animal. No oocysts were detected in bile.